The sum 16nΣ2nk=04k( 1/2k)(-1/2k)(-2k 2n-k): A computer assisted proof of its closed form, and some generalised results - Koepf, Wolfram A.; Larcombe, Peter J. (Utilitas Mathematica, 2009)
We present a second proof of an interesting binomial coefficient identity which is computer assisted, together with two related generalised results also generated computationally.